Laparoscopic hysterectomy in the overweight and obese: does 3D imaging make a change? - Berlit, Sebastian; Hornemann, Amadeus; Sütterlin, Marc; Weiß, Christel; Tuschy, Benjamin (Archives of gynecology and obstetrics, 2016)
PurposeTo evaluate the influence of three-dimensional (3D) high-definition (HD) visualisation in laparoscopic hysterectomy in normal weight, overweight and obese women.MethodsA retrospective analysis of 180 patients undergoing total laparoscopic hysterectomy (TLH: n = 90) or laparoscopic supracervical hysterectomy (LASH: n = 90) was performed. The study collective consisted of 90 women (TLH: n = 45, LASH: n = 45), who underwent laparoscopic hysterectomy with a 3D HD laparoscopic system. Ninety matched (uterine weight, previous surgeries) women with hysterectomy (TLH: n = 45, LASH: n = 45) performed by the same surgeon with conventional two-dimensional laparoscopy formed the control group. Statistical analysis was accomplished stratifying patients according to body mass index (BMI) (≤24.9, 25-29.9, ≥30.0 kg/m2). In each BMI, collective subtypes of surgery (TLH, LASH) as well as hysterectomies as a whole were analysed. Demographic data and surgical parameters were evaluated.ResultsIn all BMI subgroups, there were no significant differences concerning demographic parameters. Number of trocar site incisions needed was significantly less in women undergoing 3D compared to 2D laparoscopy independent of BMI. Furthermore, a significantly lower blood loss was revealed using 3D visualisation in LASH subgroups of the normal and overweight collectives. Three-dimensional laparoscopy was additionally associated with a significantly shorter duration of surgery in the TLH subgroup in overweight patients and a lower haemoglobin drop in the LASH subgroup of the obese.ConclusionThe need of less trocar site incisions concerning all weight groups as well.
Gesehen am 16.05.2018